Freud's Mourning and Melancholia and Arissa’s Loss and Grief in Shaila Abdullah’s Saffron Dreams - Setiawan, Badrani Tatsbita Aqwiya; Ali, Bulan Ramadhani; Tanjung, Anita Anastasyah; Elzieny, Asmaa Muhammad Othman (UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to discover the mourning and melancholia that the main character, Arissa, experiences in Shaila Abdullah’s Saffron Dreams (2009). By using close textual analysis, we investigate the ideas of loss and grief as well as the struggles of Arissa lives in the US and how she solves her problems. This research engages with Sigmund Freud’s theory that discusses about mourning and melancholia in Abdullah’s novel. The findings reveal that Faizan's death was the beginning of the problems faced by Arissa. She felt unable to live forward because she felt her world collapsed immediately and her dreams had vanished together with Faizan's death. In this novel, Arissa's melancholia appears whenever memories of Faizan come, and it affects her mind. However, the relationship between mourning and melancholia is formed due to Faizan's sudden death in the 9/11 tragedy in the Unites States, and the birth and presence of Raian have relieved Arissa's sorrowful and miserable since Faizan's death. Moreover, Raian is a significant factor in eliminating Arissa’s mourning and melancholia in the novel. Thus, Abdullah’s novel can be used an example to understand Freud’s mourning and melancholia that the protagonist’s experiences and struggles to solve her conflict within herself and beyond as a Muslimah-American who struggles to survive because of mourning and melancholia after 9/11.